THE UNDERSTANDING OF THE MUSLIM SOCIETY OF THE BREASTFEEDING VERSES IN THE QURÁN A STUDY ON BREASTFEEDING MOTHERS IN YOGYAKARTA - Rika Astari; Betty Mauli Rosa Bustam; Djamaluddin Perawironegoro; Arie Nugroho (Balai Penelitian dan Pengembangan Agama Jakarta, 2023)
As a country with a majority Muslim population, it is alleged that the level of understanding of the Indonesian Muslim community towards the verses of the Qur'an is low. The religiosity potential of people who have strong religious beliefs has not been utilized as a means of socializing the urgency of exclusive breastfeeding. One of the districts in Yogyakarta (Kulonprogo), has a high stunting rate in children, as a result of a lack of intake of breast milk in infants. This article aims to show the form of understanding of Yogyakarta Muslim mothers towards the verses of breastfeeding in the Qur'an and the factors of understanding these verses. This research uses a qualitative descriptive approach. Participants in the study consisted of 90 people, namely breastfeeding mothers in the districts of Sleman, Bantul, Kulonprogo, Gunung Kidul), and the city of Yogyakarta. The case study approach used data analysis. The low understanding of mothers about the commands and benefits of breastfeeding in the Qur'an has been caused by the low role of religious scholars/resources in bringing up the topic of breastfeeding commands, breastfeeding is part of worship in the Qur'an. This research has provided a new perspective in breastfeeding research that has so far been seen from a health perspective. This research seeks to combine health and religious approaches in understanding the benefits of breastfeeding. This paper recommends that it is necessary to optimize the role of Islamic scholars in studying the command to breastfeed in the Qur'an.